Chemical attributes of soils in long-term crop-livestock integration (Research, Society and Development, 2020)
The objective was to evaluate the chemical attributes of soils in an area with the adoption of integrated agricultural production systems of long-term, comparing land use with pasture and native forest. The study was carried out in areas managed by five agricultural technicians from the Southwest of Paraná, who adopted the crop-livestock integration system (ILP) and received guidance on soil management practices for 12 years. In each locality, soils under ILP, pasture (PV) and native forest (MN) were sampled to determine pH, Ca, Mg, K, P, base saturation (V%) and aluminum (m%) and soil organic matter (MOS) content. The adoption of the ILP systems, provides adequate levels of the chemical attributes of the soils, mainly for pH, V%, m%, Ca, Mg, K and MOS. It was also identified cases of use of high doses of poultry litter as fertilizer, with high levels of soil surface, which can generate environmental problems.